Angiographic profile of young patients (≤ 40 years) in a tertiary care center of Nepal - Rauniyar, Binay Kumar; Kadel, Arun; Acharya, Kiran Prasad; Thakur, Kartikesh Kumar; Adhikari, Rakesh Bahadur; Limbu, Deepak; Rajbhandari, Sujeeb; Kansakar, Subodh; Adhikari, Chandra Mani; Maskey, Arun; et al. (Asian Journal of Medical Sciences, 2020)
Background: With rise in prevalence of conventional risk factors like diabetes, hypertension, smoking, dyslipidemia and obesity the incidence of coronary artery disease in young patients have increased in the recent decades even in developing world. There have been multiple studies done in Nepal studying the angiographic profile of coronary disease in general population. However, only few studies has been done till date on the angiographic profile in the young population in our country. Aims and Objectives: In this study, we aim to determine the angiographic profile of young patient ≤ 40 years in a tertiary care centre of Nepal. Materials and Methods: A retrospective analytic study was done in Shahid Gangalal National Heart Centre from January 2019 to December 2019. Individuals of both genders with age ≤ 40 years who underwent coronary angiography were included. Results: Total 109 patients were included. Out of 109, 89 were male and 20 were female. The mean age for male was 35.55 ± 4.31 and for female was 38.55 ± 1.90 (P = 0.003). Among 61 (55.96%) patients who had significant coronary artery disease, 33 patients (30.27%) with single vessel disease, 15 patients (13.76%) had double vessel disease, and 13 patients (11.92%) had triple vessel disease. Left anterior descending (LAD) artery was found to be most frequently involved in all patterns of Coronary artery disease (CAD). Smoking was the most common coronary risk factor present in 29.3% of patients followed by hypertension, family history of premature CAD and diabetes in 14.6%, 7.5% and 5.5% of patients respectively. Overall, the prevalence of smoking was more in males (31.4%) than in females (20%). Conclusion: Single vessel disease (SVD) was most prevalent in young patients with significant CAD. LAD is the most commonly involved coronary artery followed by Right coronary artery (RCA) and Left Circumflex (LCX).